A Literature Review on the Role of Job Commitment in Mediating the Effects of Psychological Capital and Organizational Support on Innovative Behavior at the Information and Communication Technology Center of the Ministry of Education, Culture, Research, and Technology - Laily Musyrifah; Osly Usman (Publikasi Indonesia, 2026)
In today's rapidly changing organizational landscape, innovation has become a key determinant of competitiveness and sustainability, especially in technology-based public sector organizations. However, fostering innovative work behavior remains a challenge that requires a deep understanding of the psychological and organizational factors that drive it. This research aims to analyze the role of psychological capital and perceived organizational support in encouraging innovative work behaviors with work involvement as a mediating variable in the context of technology-based public organizations. The method used was a non-systematic literature review by analyzing 16 Scopus indexed journal articles relevant to the research variables. The analysis process is carried out through narrative synthesis techniques and thematic analysis to identify patterns of relationships between variables and gaps in the literature. The results showed that psychological capital had a strong relationship with innovative behavior, while perceived organizational support played an external factor that favored the formation of an individual's psychological condition. Additionally, work engagement has been shown to serve as a mediation mechanism that connects individual and organizational resources with innovative behaviors. These findings also show that the relationships between variables are integrative and cannot be partially explained. The conclusions of this study emphasize the importance of integrating psychological resources, organizational support, and work attachment in driving employee innovation. This research contributes to the development of conceptual models of organizational behavior as well as practical implications for innovation-based human resource management.